Effect of Tool Diameter and Feeding Speed on Surface Roughness in the AISI 1045 Steel Milling Process - Iswanto, Iswanto (METAL: Jurnal Sistem Mekanik dan Termal, 2023)
This paper discusses how the influence of the tool diameter on the surface roughness of the workpiece, how the effect of feeding speed on the surface roughness of the workpiece and whether there is an interaction between the tool diameter and feeding speed on the workpiece surface roughness in the AISI 1045 steel milling process. Variables that are varied in this study were the tool diameter, namely 6 mm, 8 mm, and 10 mm and the variation of feeding speed used was 33.5 mm/min, 59.4 mm/min and 111.9 mm/min. After the AISI 1045 steel milling process by varying the specified parameters, and then the surface roughness test of the workpiece is carried out. From the results of research that has been done, it can be concluded that, tool diameter and feeding speed together have a significant effect on the surface roughness of the workpiece in the AISI 1045 steel milling process.